(untitled) - Phillips, Deborah (Pearson Education, Inc, 2002)
This complete multimedia TOEFL course aims to help students prepare for both the paper and computer versions of the TOEFL test. The text features language skills, practice exercises, test-taking strategies, and pre- and post-tests. The CD-ROM includes practice and test questions.
Keywords: English language; Examinations,Study guide